Antigen-dependent versus -independent activation of iNKT cells during infection - Holzapfel, Keli L. (2014)
CD1d-reactive invariant natural killer T cells (iNKT) play a vital role in determining the characteristics of immune responses to infectious agents. Previous reports suggest that iNKT cell activation during infection can be: 1) solely driven by cytokines from innate immune cells; 2) require microbial-antigen; or 3) require self-antigen. In this study, we examined the role of antigen receptor stimulation in iNKT cells during several bacterial and viral infections. To test for antigen receptor signaling, Nur77(gfp) BAC transgenic mice, which upregulate GFP in response to antigen receptor but not inflammatory signals, were analyzed. iNKT cells in the reporter mice infected with mouse cytomegalovirus (MCMV) produced IFNγ but did not upregulate GFP, consistent with their reported CD1d-independent activation. However, two bacteria known to produce lipid antigens for iNKT cells induced GFP expression and cytokine production. In contrast, although Salmonella typhimurium (S. typhimurium) was proposed to induce the presentation of a self-lipid, iNKT cells produced IFNγ, but did not upregulate GFP after infection in vivo. Even in CD1d-deficient hosts, iNKT cells were still able to produce IFNγ after S. typhimurium infection. Furthermore, while it has been proposed that endogenous lipid presentation is a result of Toll-like receptor (TLR) stimulation of antigen presenting cells, injection of different TLR agonists led to iNKT cell IFNγ but not increased GFP expression. These data indicate that robust iNKT cell responses to bacteria as well as viruses can be obtained in the absence of antigenic stimulation.